Comparison of standard short infusion versus prolonged infusion of Doxorubicin in relation to its cardiotoxicity in South Indian population - Jacob, Roshan Koshy; Karpurmath, Shashidhar V.; Nandennavar, Manjunath; Angadi, Veerendra (International Journal of Research in Medical Sciences, 2019)
Background: Anthracycline is one of the commonly used chemotherapeutic agents in the treatment of malignancies and their efficacy is undermined by potential life-threatening cardiotoxicity. The aim of this study is to compare the cardiotoxicity in patients receiving standard short infusion (15-30 minutes) versus prolonged infusion (6 hours) of doxorubicin in the study group. Methods: In this study 80 patients who were planned for treatment with Doxorubicin >200 mg/m2 were included in this study and they were randomly allotted to either of the treatment group. Each patient was assessed clinically (History, Pulse rate, Blood pressure) along with ECG ,ECHO prior to initiation of chemotherapy, after completion of 200 mg/m2 of Doxorubicin, 3 months and 6 months after chemotherapy. Results: There were 40 patients in each group, and they received a total of 384 cycles of Doxorubicin containing regimens according to respective protocols. The median number of cycles was four (range four to six cycles). The mean cumulative dose of doxorubicin was 271.5 mg/m2 in the group which received standard short infusion and 264 mg/m2 in the group which received the drug by prolonged infusion. However, none of the patients developed any cardiac symptoms during or after the planned chemotherapy nor was there a drop in ejection fraction on serial ECHO. Conclusions: There was no benefit of prolonged infusion of doxorubicin as compared to the standard rapid infusion in terms of doxorubicin induced cardiotoxicity. At present, standard rapid infusion is the best option.